2002
DOI: 10.3354/meps232015
|View full text |Cite
|
Sign up to set email alerts
|

Soft-sediment benthic biodiversity on the continental shelf in relation to environmental variability

Abstract: Soft-sediment macrobenthos data for the Norwegian continental shelf (61°N, 1 to 2°E) was used to examine species distributions, community structure and community differences, and how different measures of biodiversity are related to environmental variability. Water depth at 35 sites ranged from 115 to 331 m over a spatial sampling scale of ca. 45 km × 60 km, and there was considerable variation in sediment characteristics. Of a total of 508 recorded species, 39% were restricted to 1 or 2 sites, whereas only 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
140
1
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(162 citation statements)
references
References 47 publications
15
140
1
6
Order By: Relevance
“…Massad and Brunel (1979) and Robert (1979) also noticed increased richness with sand content which were independent of bathymetric position but, Bergen et al (2000) and Ellingsen (2002) observed that depth was the primary habitat factor organizing the southern California and Norwegian benthic community respectively followed by sediment grain size and not much effected by latitude. Ellingsen (2002) added that biotic factors such as availability and abundance of benthic larvae/adult might be more important than sediment characteristics in determinining benthic settlement. Dominance of polychaete species was high in deeper depths especially from family Spionidae, Cirratulidae and Capitellidae showed ability of these species in adverse conditions.…”
Section: Discussionmentioning
confidence: 97%
“…Massad and Brunel (1979) and Robert (1979) also noticed increased richness with sand content which were independent of bathymetric position but, Bergen et al (2000) and Ellingsen (2002) observed that depth was the primary habitat factor organizing the southern California and Norwegian benthic community respectively followed by sediment grain size and not much effected by latitude. Ellingsen (2002) added that biotic factors such as availability and abundance of benthic larvae/adult might be more important than sediment characteristics in determinining benthic settlement. Dominance of polychaete species was high in deeper depths especially from family Spionidae, Cirratulidae and Capitellidae showed ability of these species in adverse conditions.…”
Section: Discussionmentioning
confidence: 97%
“…This necessity has led to the development of different indexes based on soft-bottom communities, which summarise ecological status and ecological quality. The relationships between macrofaunal assemblages and the effect of contaminants on them have been described extensively in the literature, (Pearson and Rosenberg, 1978;Gray and Mirza, 1979;Dauvin, 1982;Warwick et al, 1990;Simboura et al, 1995;Estacio et al, 1997;Ellingsen, 2002;Morrisey et al, 2003;Guerra-García and García-Gómez, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Gray, 1974;Ellingsen, 2002;Blanchet et. al., 2005;Lu, 2005;Munari et al, 2005), principalmente pelas características texturais dos sedimentos, a salinidade, a profundidade, o pH e o oxigênio dissolvido.…”
Section: O Bentos Estuarinounclassified
“…(e.g. Gray, 1974;Snelgrove e Butman, 1994;Ellingsen, 2002). Estes fatores promovem uma grande heterogeneidade de ambientes, criando vários tipos de habitats e, consequentemente, determinando a variabilidade em diferentes escalas.…”
Section: O Bentos Estuarinounclassified